Needs Analysis of Early Childhood Education Teachers Regarding the Integration of Acehnese Heroic Values in Character Education - Elfiadi Elfiadi; Panggung Sutapa; Nur Hayati; Anisaturrahmi Anisaturrahmi (Jurnal Pendidikan Anak, 2026)
Patriotism in early childhood is a key foundation for social cohesion and national identity. However, integrating local cultural values into character education remains a challenge in many early childhood settings. This study explores early childhood education teachers’ needs for integrating Acehnese heroic values into character learning. A mixed-methods sequential explanatory design was employed, involving a survey of 86 kindergarten teachers in North Aceh, followed by focus group discussions (FGD) and in-depth interviews. The findings revealed three main themes: (1) learning practices were largely dominated by conventional approaches, with limited use of Acehnese heroic narratives; (2) teachers faced challenges related to inadequate training in contextual pedagogy, limited learning resources, and difficulties in designing meaningful learning activities; and (3) most teachers expressed a strong need for innovative learning models grounded in local wisdom, active child participation, and practical teaching guidelines. The study identifies three key areas of need: content, pedagogy, and system support. Its main contribution lies in linking teachers’ needs analysis with local heroic values as a foundation for integrating character education into early childhood learning.